PCDHB14- and GABRB1-like nervous system developmental genes are altered during early neuronal differentiation of NCCIT cells treated with ethanol. (October 2015) - Halder, D; Mandal, C; Lee, BH; Lee, JS; Choi, MR; Chai, JC; Lee, YS; Jung, KH; Chai, YG
Ethanol (EtOH) exposure during embryonic development causes dysfunction of the central nervous system (CNS). Here, we examined the effects of chronic EtOH on gene expression during early stages of neuronal differentiation. Human embryonic carcinoma (NCCIT) cells were differentiated into neuronal precursors/lineages in the presence or absence of EtOH and folic acid. Gene expression profiling and pathway analysis demonstrated that EtOH deregulates many genes and pathways that are involved in early brain development. EtOH exposure downregulated several important genes, such as PCDHB14, GABRB1, CTNND2, NAV3, RALDH1, and OPN5, which are involved in CNS development, synapse assembly, synaptic transmission, and neurotransmitter receptor activity. GeneGo pathway analysis revealed that the deregulated genes mapped to disease pathways that were relevant to fetal alcohol spectrum disorders (FASD, such as neurotic disorders, epilepsy, and alcohol-related disorders). In conclusion, these findings suggest that the impairment of the neurological system or suboptimal synapse formation resulting from EtOH exposure could underlie the neurodevelopmental disorders in individuals with FASD.